Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Matematika Materi Bilangan Desimal Metode Demonstrasi Siswa Kelas IVA UPT SD Negeri 028 Kubang Jaya - Desi Arisandi (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2024)
The aim of this research is to describe and analyze students' relatively permanent attitudes or behavior from experience or training with Decimal Number material through the application of the demonstration method. This research method uses qualitative research with the type of Classroom Action Research. Primary data source for students and teachers in class IV A. Data collection techniques used observation, interviews and documentation. Data analysis techniques use data reduction, data triangulation, and data collection. The repairs were carried out in class IVA UPT SD Negeri 028 Kubang Jaya, Siak Hulu District, Kampar Regency with a total of 39 students consisting of 20 male students and 19 female students. The results of data findings using the analysis and problem formulation above show that the learning improvement program is carried out by teachers to improve student learning outcomes in Mathematics subject matter. The application of the demonstration method and the use of decimal number image media can improve student learning outcomes for Decimal Numbers in Mathematics subjects. Results achieved by students after applying the demonstration method. Changes in student learning outcomes after using the demonstration method.